FAKTOR-FAKTOR YANG MEMPENGARUHI SANTRI BERSEKOLAH DI PONDOK PESANTREN BAHRUL ULUM KAMPUNG SAWIT PERMAI KECAMATAN DAYUN KABUPATEN SIAK - Try Sugiyatmi; Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in Sawit Permai Villages of Dayun district Siak Regency with a problem that: first, what is the Socioeconomic background of the families of Students attending boarding schools Bahrul Ulum in Permai Palm? Second, what are the factors of Internal and external factors that affect students attending Bahrul Ulum boarding school in sawit Permai villages of Dayun district Siak Regency? The purpose of this research is to know the background of socioeconomic of Students family that attended Bahrul Ulum boarding school in sawit Permai villages and to find out internal factors and external factors that affect Students attending Bahrul Ulum boarding school in sawit Permai villages of Dayun district Siak Regency. This research is a descriptive quantitative. Population of this research are Santri MTs class VII and VIII totaled 107 and 107 MTs students parents and MA class X and class XI 42 and 42 MA students parents. So, total population 298, population was taken with the technique that Proportionate Stratified Random Sampling that is taking a Sample by observing the Strata (level) in the Heterogeneous population (not similar). While the Sample in this study i.e. 54 Santri MTs, 54 parents Students from sample Santri MTs (50%) and 21 Students of MA, 21 students parents from the sample as many MA Students (50%). So overall population i.e. tolah 150 respondents. To collect data using a penelti questionnaire and documentation.The result of this research shows that the variables X1 socio-economic background of Students may not MTs Family because count t > 0.213 > 0.05 0.05 IE so that the variable X 1 is not significant. The variable X2 MTs internal factors significant because t count < 0.05 i.e. 0.000 < 0.05 so significant or influential variables X2 and X3 Variable external factors significant MTs t calculate > 0.05 i.e. 0.000 < 0.05 so significant or influential variables X3. Variables X1 Family Socioeconomic Background Students may not because M t calculate > 0.05 i.e. 0.82 > 0.05 so that the variable X 1 is not significant. The variable X2 internal factors significant because MA t count 0.000 i.e. 0.05 < < 0.05 so significant or influential variables X2 and X3 Variable external factors significantly MA t calculate > 0.05 0.05 0.000 i.e. variable X3 so < significant or influential.Keywords: Interest, Decision, Students